THE IMPORTANCE OF PEAK INSPIRATORY FLOW ASSESSMENT IN REAL-TIME CLINICAL PRACTICE - Mambetniyazov K.S; Liverko I.V (Western European Studies, 2025)
In order to assess peak inspiratory flow (PIF) in 100 patients with obstructive respiratory pathology as part of the selection of an inhalation device for optimizing inhalation respiratory therapy, a functional study of PIF was conducted using the In-Check DIAL device (Clement Clarke International Ltd., UK) with an imitation of an inhaler of resistance on inspiration, where the device panel took into account the flows: R0 without resistance and 4 levels of resistance, including R1 - low resistance, R2 - medium-low, R3 - medium, R4 - medium-high resistance. The results of the clinical study showed a high proportion of patients (34%-85%) whose peak inspiratory air flow when using inhalers is below the level required for optimal inhalation through inhalation devices with medium-low, medium and medium-high resistance, as a result of which patients receive an insufficient dose of drugs, they experience more frequent exacerbations and hospitalizations compared to patients who are able to create an inhalation flow adequate to the resistance of the inhaler. Suboptimal values of peak inspiratory flow, determined by phenotypic predictors, including female gender, height less than 1.6 m, BMI less than 20 kg/m2 or more than 30 kg/m2, age over 70 years, clinical and functional markers, including the degree of clinical severity of dyspnea according to mMRC more than 3 points, the severity of obstructive disorders FEV1 less than 50% of the expected, and the features of the clinical course, characterized by a high frequency of exacerbations requiring 2 or more hospitalizations, are declared the main component for choosing an inhalation device with optimal resistance, ensuring the effectiveness of therapy for obstructive respiratory pathology, including COPD and asthma, a predictor of treatment effectiveness, optimization of control and a decrease in the frequency of exacerbations requiring frequent hospitalizations. Evaluation of peak inspiratory flow in patients with obstructive respiratory pathology, based on phenotypic, clinical and functional characteristics and variants of the disease course, and its suboptimal peak inspiratory flow in comparison with the level of inhaler resistance can help clinicians to personalize the selection of an inhaler in patients with exacerbation of obstructive respiratory pathology and optimize the choice of an inhalation device in a stable course of the disease.
Keywords: peak inspiratory flow; suboptimal peak inspiratory flow; metered-dose inhaler